2010
DOI: 10.2174/138161210790883570
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of a Diet with Inulin-Enriched Pasta in Healthy Young Volunteers

Abstract: Different lines of evidence suggest that higher intake of fiber may somehow protect against metabolic syndrome. The prebiotic inulin has widely been studied in relation to its putative beneficial effects on lipid and glucose metabolism. Therefore, adding inulin to diet may be a suitable strategy to prevent metabolic syndrome. Aim of the present study was to evaluate the effects of the daily consumption of inulin-enriched pasta on lipid and glucose metabolism as well as on gastrointestinal motility in young hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…The cholesterollowering effect of FOS is also in agreement with the work of Russo et al (2010). They provided inulin-enriched pasta for a period of 2 wk and observed significant differences among control and the treated groups for HDL, triglycerides, cholesterol/HDL ratio and glucose level.…”
Section: Resultssupporting
confidence: 85%
“…The cholesterollowering effect of FOS is also in agreement with the work of Russo et al (2010). They provided inulin-enriched pasta for a period of 2 wk and observed significant differences among control and the treated groups for HDL, triglycerides, cholesterol/HDL ratio and glucose level.…”
Section: Resultssupporting
confidence: 85%
“…Additionally, gastric emptying was significantly delayed in the treated group. The study provided evidence that prebiotics enriched pasta modulated lipid and glucose metabolism along with insulin resistance (Russo et al, 2010). Earlier, Causey, Feirtag, Gallaher, Tungland, and Slavin (2000) explored the impact of inulin from chicory root on serum lipid parameters and faecal composition in hypercholesterolaemic subjects.…”
Section: Substrate Subjects/animals Dose/duration Results Referencementioning
confidence: 95%
“…It is composed of several plant extracts ( Curcuma , silymarin, guggul, chlorogenic acid and inulin) that exert, at least individually, beneficial effects on different components of MetS. Curcumin improves insulin resistance and dyslipidemia [26]; silymarin exerts anti-inflammatory effects in animal models of NAFLD [27]; guggul lipids have been successfully used in obesity and hypercholesterolemia [28]; and chlorogenic acid, as well as inulin, may improve lipidic and glycidic metabolism [29,30]. In the present study, we have demonstrated that the diet natural supplement is able to prevent body weight gain, hepatic fat accumulation, atherosclerotic lesions development and dysregulation of lipidic metabolism.…”
Section: Discussionmentioning
confidence: 99%